2007
DOI: 10.1121/1.2722209
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in vowel perception and production: A study of accent change in young adults

Abstract: This study investigated changes in vowel production and perception among university students from the north of England, as individuals adapt their accent from regional to educated norms. Subjects were tested in their production and perception at regular intervals over a period of 2 years: before beginning university, 3 months later, and at the end of their first and second years at university. At each testing session, subjects were recorded reading a set of experimental words and a short passage. Subjects also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
135
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 27 publications
11
135
0
Order By: Relevance
“…Evans and Iverson (2007) investigated vowel perception and production amongst university students from the north of England, as they adapted their accent from regional to educated (i.e., SE) norms. Participants were tested in their production and perception at regular intervals over a period of two years using a battery of tests.…”
Section: Familiarity With a Native Accent And Speech Comprehensionmentioning
confidence: 99%
“…Evans and Iverson (2007) investigated vowel perception and production amongst university students from the north of England, as they adapted their accent from regional to educated (i.e., SE) norms. Participants were tested in their production and perception at regular intervals over a period of two years using a battery of tests.…”
Section: Familiarity With a Native Accent And Speech Comprehensionmentioning
confidence: 99%
“…Second, we chose only speakers who did not change their place of residence, to avoid different accent influences (cf. Clopper and Pisoni 2006;Evans and Iverson 2007). The EFL speakers have acquired English only in academic settings; all the other speakers acquired English in naturalistic settings.…”
Section: Choice Of Speakersmentioning
confidence: 99%
“…What happens to adults' more fully-formed linguistic systems in cases of dialect contact has been examined as well (Trudgill 1986;Munro et al 1999;Evans and Iverson 2007). Studies have found that adults acquire some features of the new dialect, but rarely, if ever, do the adults fully acquire the new dialect.…”
Section: Introductionmentioning
confidence: 99%